Modelos de Heterocedasticidad condicional en el pronóstico del Comportamiento del precio del Petróleo en el Ecuador - Noriega Jurado, Josue Fernando (2019)
In the investigation is carried out an analysis of the series of the price of oil barrel in Ecuador in the period 2015-2019, where its behavior is described as well as the political and economic context under which all the events that were related to the price of the of hydrocarbon were developed. In addition, it details the operation of the worldwide oil market, as well as the factors that impact the price of an oil barrel. On the other hand, are explained the conditional heteroscedasticity models ARCH, GARCH and their importance in the forecast of financial series. Then, the GARCH model is identified as the most efficient method to predict the behavior of the oil price in Ecuador and, the econometric model is run through the Eviews 9 program, taking as reference the quotation in working days, which starts from January 2, 2015 until June 3, 2019. As a result of the estimation, it is obtained that the series will present an increasing trend during the following 22 days.